2009
DOI: 10.2500/ajra.2009.23.3370
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Bulb Volume in Taiwanese Patients with Posttraumatic Anosmia

Abstract: OB volumes were significantly lower in Taiwanese patients with posttraumatic anosmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…16 According to this theory, the observed findings of decreased volume of the olfactory bulb in these patients may be caused by decreased sensory input. 17 However, a recent report of delayed anosmia several weeks after trauma and MRI showing scarring in the region of the olfactory bulb indicate that direct brain trauma could also be a relevant factor in some cases. 16 A role for direct brain injury is also supported by many studies showing abnormalities on MRI in frontal lobes as well as olfactory bulbs, and a recent study with single-photon emission CT even demonstrated hypoperfusion of parietal and temporal lobes in patients with posttraumatic anosmia compared with patients with similar trauma but normal sense of smell.…”
Section: Common Etiologies/associationsmentioning
confidence: 97%
See 1 more Smart Citation
“…16 According to this theory, the observed findings of decreased volume of the olfactory bulb in these patients may be caused by decreased sensory input. 17 However, a recent report of delayed anosmia several weeks after trauma and MRI showing scarring in the region of the olfactory bulb indicate that direct brain trauma could also be a relevant factor in some cases. 16 A role for direct brain injury is also supported by many studies showing abnormalities on MRI in frontal lobes as well as olfactory bulbs, and a recent study with single-photon emission CT even demonstrated hypoperfusion of parietal and temporal lobes in patients with posttraumatic anosmia compared with patients with similar trauma but normal sense of smell.…”
Section: Common Etiologies/associationsmentioning
confidence: 97%
“…Prognosis for recovery of normal function in head trauma-related anosmia is also poor, with there generally being little if any response even to systemic steroids. 16,17,27 Early research currently underway into the possibility of surgical approaches to restore olfactory function such as transplantation of the olfactory epithelium does offer some hope for future developments. 27 As mentioned previously, there is some improvement in anosmia associated with chronic rhinosinusitis with endoscopic sinus surgery and polyp removal, especially if one looks at symptom scores, with less effect on more detailed measures of olfactory function.…”
Section: Treatmentmentioning
confidence: 99%
“…Thus, olfactory bulb volume is reduced in cigarette smokers (Schriever et al, 2013) and in those with a number of neurological diseases or other disorders (Yousem et al, 1995b). These include acute depression (Negoias et al, 2010), Alzheimer's disease (Thomann et al, 2009), childhood abuse (Croy et al, 2013), chronic sinusitis (Rombaux et al, 2008), congential anosmia with and without Kallmann syndrome (Yousem et al, 1993, 1996; Abolmaali et al, 2002; Koenigkam-Santos et al, 2011; Levy et al, 2013), epilepsy (Hummel et al, 2012), head trauma (Yousem et al, 1995a; Doty et al, 1997; Landis et al, 2005; Jiang et al, 2009), multiple sclerosis (Goektas et al, 2011; Schmidt et al, 2011), Parkinson's disease (Wang et al, 2011b; Brodoehl et al, 2012), polyposis (Herzallah et al, 2013), schizophrenia (Turetsky et al, 2003; Nguyen et al, 2011), and prior upper respiratory infections associated with chronic smell loss (Rombaux et al, 2009). Such studies strongly suggest that olfactory bulb volume is a marker for olfactory function in general (Yousem et al, 1998; Turetsky et al, 2003; Buschhuter et al, 2008; Haehner et al, 2008; Hummel et al, 2011; Rombaux et al, 2012).…”
Section: Causes Of Age-related Olfactory Lossmentioning
confidence: 99%
“…Peripherally in the nose, stretching or shearing of the olfactory nerves as they traverse the skull base may occur in the course of a sudden head contusion [61] . Finally, a decreased volume of the olfactory bulb may be caused by decreased sensory input [62] . We note that surgery to the nose or brain may induce similar “traumatic” changes to olfactory function.…”
Section: Risk Factors That Have Been Associated With Olfactory Disordersmentioning
confidence: 99%